PERANCANGAN ALAT PERAGA DIFFERENTIAL THERMAL ANALYSIS UNTUK ANALISIS TITIK LELEH MATERIAL INDIUM, TIMAH DAN SENG - Hidayanti, Fitria; Yulianto, Tri; Wismogroho, Agus Sukarto (Sainstek : Jurnal Sains dan Teknologi, 2016)
The aims this research was to designed a differential thermal analysis props to analyze the melting point of the material. Differential Thermal Analysis props have a furnace with a maximum temperature of 600 ° C. Temperature sensor used is a K-type thermocouple with a measurement range of -200 ° C to 1200 ° C. Controller is used to control the temperature of the furnace is Autonics with digital temperature controller type TK4M. Measurement of the value of the temperature in the furnace using an Arduino Uno microcontroller connected to LabVIEW software via USB. Measurement of the melting point of the material used these props are tested on material Indium (In), tin (Sn), and zinc (Zn) with a melting point 152,50C, 231,50C and 4250C.